2015
DOI: 10.1155/2015/581697
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical Migration of Missed Intrauterine Device Associated with Stone Formation: A Case Report and Review of the Literature

Abstract: Intrauterine device is the most widely used method of reversible contraception. It may cause various complications including perforation of uterus. In this case, 44-year-old woman was presented with lower urinary tract symptoms after six years of insertion. Patient has no remarkable physical or laboratory finding but abdominal ultrasound revealed a 27 mm hyperechogenicity, suggestive of foreign body or calculus on the posterior bladder wall which was removed endoscopically. This case highlights the need of imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 18 publications
0
18
0
2
Order By: Relevance
“…7 The interval between insertion and occurrence of symptoms varies, from 6 months up to 16 years. 1,8 There are two main mechanisms of uterine perforation. First, perforation may occur during IUD insertion, of which termed misplacement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 The interval between insertion and occurrence of symptoms varies, from 6 months up to 16 years. 1,8 There are two main mechanisms of uterine perforation. First, perforation may occur during IUD insertion, of which termed misplacement.…”
Section: Discussionmentioning
confidence: 99%
“…Voiding symptoms, such as pain during urination, combined with a history of unretrieved IUD may be indicative of possible perforation of the uterus and intravesical IUD. 8 There are several risk factors associated with uterine perforation by IUD. Insertion by a less experienced physician, lactation, postpartum insertion (< 6 months since delivery), lower parity and higher number of previous abortions are associated with risk of uterine perforation.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients with intra bladder IUD are symptomatic with recurrent or persistent UTI and its symptoms, being the most common presentation [23]. Kart hematuria [19]. Gunbey et al reported a case of a 46 year old woman with IUD partially embedded in the wall of the cervix and extending into the bladder lumen, presented with lower abdominal pain lasting for 2 years [24].…”
Section: Discussionmentioning
confidence: 99%
“…3,6,7 Debido a que algunas perforaciones no causan ningún síntoma clínico, las tasas de perforación reales pueden ser un poco más altas. 3,8 Una vez perforado el útero, un DIU puede migrar a las estructuras cercanas como peritoneo, epiplón, anexos, colon, vejiga y apéndice. 1,8 La migración intravesical de ese dispositivo con la formación secundaria de cálculos es una complicación extremadamente rara.…”
Section: Discusión Y Revisión De La Literaturaunclassified
“…3,8 Una vez perforado el útero, un DIU puede migrar a las estructuras cercanas como peritoneo, epiplón, anexos, colon, vejiga y apéndice. 1,8 La migración intravesical de ese dispositivo con la formación secundaria de cálculos es una complicación extremadamente rara. 9 La migración de un DIU ocurre debido a la perforación primaria traumática del útero o debido a un proceso inflamatorio crónico, cuyo mecanismo exacto no se comprende completamente.…”
Section: Discusión Y Revisión De La Literaturaunclassified